Pengaruh Efikasi Diri terhadap Kesiapan Kerja Mahasiswa Akhir Program Studi Manajemen Angkatan 2018 Fakultas Ekonomi dan Bisnis Universitas Islam Bandung - Syafira Yasinta; Aminuddin Irfani (Bandung Conference Series: Business and Management, 2022)
Abstract. Many companies require contributions from potential human resources and many of them are looking for prospective undergraduate graduates who have been confirmed to have work skills in the form of self-efficacy and good work readiness, especially human resource management graduates who know the knowledge to manage the goals of a company or organization can be achieved. This study aims to 1) To find out how the self-efficacy of the final students of the management Study Program class of 2018 at the Faculty of Economics and Business, Islamic University of Bandung. 2) To find out how the work readiness of the final students of the management study program class of 2018 at the Faculty of Economics and Business Unisba has. 3) To find out how the effect of self-efficacy on the work readiness of final year students of the management tudi program class of 2018 at the Faculty of Economics and Business, Islamic University of Bandung. The research method used is descriptive and verifiable analysis. Methods of collecting data obtained through interviews and questionnaires. The respondents in this study were 166 final management students of the class of 2018. Purposive sampling technique with slovin formula. The results of this study concluded that: 1) Self-efficacy in the final students of the management study program namely the results are "good" 2) The work readiness of the final students of the management study program are "high"3) The results of the study stated that there was a significant positive influence between self-efficacy on work readiness. Abtsrak. Banyak perusahaan yang membutuhkan kontribusi dari sumber daya manusia yang potensial dan banyak dari mereka yang mencari calon lulusan sarjana yang sudah dipastikan memiliki kulitas kerja berupa efikasi diri dan kesiapan kerja yang baik terutama para lulusan manajemen sumber daya manusia yang mengetahui ilmu untuk mengelola tujuan dari sebuah perusahaan atau organisasi dapat tercapai. Penelitian ini bertujuan 1) Untuk mengetahui bagaimana efikasi diri yang dimiliki mahasiswa akhir Program Studi manajemen angkatan 2018 di Fakultas Ekonomi dan Bisnis Universitas Islam Bandung. 2) Untuk mengetahui bagaimana kesiapan kerja yang dimiliki mahasiswa akhir Program Studi manajemen angkatan 2018 di Fakultas Ekonomi dan Bisnis Unisba. 3) Untuk mengetahui bagaimana pengaruh efikasi diri terhadap kesiapan kerja mahasiswa tingkat akhir Program tudi manajemen angkatan 2018 di Fakultas Ekonomi dan Bisnis Universitas Islam Bandung. Metode penelitian yang digunakan adalah analisis deskriptif dan verifikatif. Metode pengumpulan data yang diperoleh melalui wawancara dan kuesioner. Responden dalam penelitian ini adalah mahasiswa akhir manajemen angkatan 2018 berjumlah 166 orang. Teknik pengambilan sampel purposive sampling dengan rumus slovin. Hasil penelitian ini menyimpulkan bahwa : 1) Efikasi diri pada mahasiswa akhir program studi manajemen diketahui ternyata hasilnya “baik” 2) Kesiapan kerja yang dimiliki mahasiswa akhir program studi manajemen yakni “tinggi” 3) Hasil dari penelitian menyatakan ada pengaruh positif signifikan antara efikasi diri terhadap kesiapan kerja.